Efficient utilization of CO2 in power-to-liquids/power-to-gas hybrid processes: An economic-environmental assessment. (February 2023) - Gao, Ruxing; Zhang, Leiyu; Wang, Lei; Zhang, Chundong; Jun, Ki-Won; Kim, Seok Ki; Park, Hae-Gu; Zhao, Tiansheng; Wan, Hui; Guan, Guofeng
Abstract: Power-to-liquid (P2L) and Power-to-Gas (P2G) processes are considered as sustainable pathways to mitigate climate change. In both P2L and P2G processes, H2 production via water electrolysis has received widespread attentions, including PEM, AEM, SOEC and AWE technologies. Based on the preceding technical study on four P2L/P2G hybrid processes composed of above-mentioned water electrolysis technologies, a systematic study of P2L/P2G processes and economic analysis were conducted to quantitatively evaluate their economic performances in terms of total production cost (TPC) and net CO2 reduction cost (CRC). The P2L/P2G process coupled with SOEC technology has the lowest TPC of 204 M$/year, while that coupled with AEM technology has the lowest net CRC of 274 $/tonne CO2 . Moreover, we further proposed nine process scenarios for P2L/P2G processes using grey, blue, and green H2, and compared their process performances in terms of TPC and global warming potential (GWP). The P2L/P2G process via water electrolysis using wind electricity reduces GWP by 61.50%, whereas its TPC is 1.39 times higher than that with coal gasification due to the relatively high production cost. It is anticipated that a significant cost saving in the water electrolysis units is possible in the future, which will definitely improve the profitability of P2L/P2G process. Graphical Abstract: P2L/P2G hybrid processes composed of diverse water electrolysis technologies. ga1 Highlights: Novel P2L/P2G processes composed of four water electrolysis technologies are proposed. P2L/P2G processes with SOEC and AEM technologies have the lowest TPC and net CRC, respectively. P2L/P2G processes using grey, blue, and green H2 are compared in TPC and GWP. TPC of P2L/P2G processes using green H2 are 1.2–1.7 times higher than those using grey H2 . GWP of P2L/P2G processes using green H2 decrease by 24–64%.